Nosiale Pale Program for stunting prevention in Palu city - Moh Nawawi; Rusmawaty Bte Rusdin (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Tadulako, 2023)
The prevalence of stunting exhibits a declining trend, yet it surpasses the WHO-established standard of under 20%. The 2022 target aims for a reduction to 18%, followed by a 2024 target of 12% or below the national prevalence of 14%. According to data from the Community Based Nutrition Recording and Reporting (e-PPBGM), 1,221 out of 22,400 toddlers in Palu City were identified as stunted. This study seeks to elucidate strategies for stunting prevention in Palu City and analyze factors supporting or impeding these efforts. Employing a qualitative method, data collection involves observation, interviews, and documentation studies. The Miles and Huberman model guides data analysis through stages of collection, reduction, presentation, and verification. Interviews target the Department of Health, Health Workers, and the Community. Findings underscore the collaborative initiatives undertaken by the Palu City government to prevent and address stunting, employing the